Use of ultraviolet-C in environmental sterilization in hospitals: A systematic review on efficacy and safety - Ramos, Clysly Celine R.; Roque, Josemaria Lorenzo A.; Sarmiento, Diane B.; Suarez, Luis Enrico G.; Sunio, Janela Tanya P.; Tabungar, Kaezzy Ila B.; Tengco, Geraldine Susan C.; Rio, Phylis C.; Hilario, Allan L. (International Journal of Health Sciences, 2020)
Objectives: The study aimed to review the literature on the use of ultraviolet-C (UV-C) sterilization to assess its clinical efficacy in reducing risk and transmission of nosocomial infections as well as its associated health safety or hazards. Methods: Four main search engines were used to identify potential studies which included: (1) Google Scholar, (2) ScienceDirect, (3) PubMed, and (4) Cochrane. Studies in English and published from 2010 to 2020 were considered. Studies on efficacy were limited to those in unseeded hospital environments, examining environmental disinfection, and with true experimental, randomized controlled trial, or quasiexperimental study designs. No additional criterion was used for safety studies due to the scarcity of literature. In the end, a total of 17 studies were selected. Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines were followed. Risk of bias assessment and manual data extraction and tabulation were done. Results: Twelve eligible efficacy studies were identified together with five safety studies. It was found that UV-C irradiation had positive results when used as an adjunct for existing cleaning protocols. The germicidal effect of UV-C is potent against microorganisms including viruses, methicillin-resistant Staphylococcus aureus, and vancomycin-resistant enterococci. Safety study results showed dermal effects of UV-C exposure including DNA lesions, formation of cyclobutane pyrimidine dimers in cells, and effects on the skin’s stratum corneum. Conclusion: It was found that UV-C can be utilized as an adjunct to terminal manual cleaning because of its efficacy as a germicidal agent. Further studies must still be done to exact a standard for safe exposure dose, especially for 222 nm germicidal lamps. Direct evidence is needed for any targeted implementation of UV-C during Coronavirus Disease 2019 (COVID-19) pandemic.